2000
DOI: 10.1108/14637150010345488
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity as a tool for business process reengineering

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…However, they differ in the way this should be done. While Kaizen is primarily focused on efficiency and on avoiding customer dissatisfaction, effectiveness and customer satisfaction are the main concentration of re-engineering (Rohleder and Silver, 1997;Martinez et al, 1999;Murray et al, 2000). In others words, BPR seeks to ensure that the right things are being done (effectiveness), while Kaizen seeks to ensure that the right things are done well (efficiency).…”
Section: Differences Between Six-sigma Dmaic Methodology and Design Fmentioning
confidence: 99%
“…However, they differ in the way this should be done. While Kaizen is primarily focused on efficiency and on avoiding customer dissatisfaction, effectiveness and customer satisfaction are the main concentration of re-engineering (Rohleder and Silver, 1997;Martinez et al, 1999;Murray et al, 2000). In others words, BPR seeks to ensure that the right things are being done (effectiveness), while Kaizen seeks to ensure that the right things are done well (efficiency).…”
Section: Differences Between Six-sigma Dmaic Methodology and Design Fmentioning
confidence: 99%
“…Research [48] reported such experience in applying nonlinear systems theory in health care settings. This research revealed that nonlinear science offered a practical new frame of reference for BPR initiatives.…”
Section: B Business Process Modeling Attemptsmentioning
confidence: 99%
“…Άλλες ερευνητικές προσπάθειες βασίζονται στη θεωρία της μη γραμμικότητας, προκειμένου να διευκολύνουν την ανάπτυξη συλλογιστικής γύρω από την επίδραση της μεταβολής των διαδικασιών και του νέου μοντέλου λειτουργίας της επιχείρησης. Οι Murray, Priesmever, Sharp, Jensen και Jensen αναφέρονται στην εμπειρία από την εφαρμογή της θεωρίας μη γραμμικών συστημάτων στον τομέα της περίθαλψης [122]. Η έρευνά τους αποκαλύπτει ότι η θεωρία της μη γραμμικότητας προσφέρει ένα νέο πλαίσιο αναφοράς για τις πρωτοβουλίες Διδακτορική Διατριβή BPR.…”
Section: προσπάθειες αναπλήρωσης των μεθοδολογιών Bprunclassified